2014
DOI: 10.1089/pop.2013.0021
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Effective Clinical Registries to Advance Medical Care Quality and Transparency

Abstract: Policy makers, payers, and the general public are increasingly focused on health care quality improvement. Measuring quality requires robust data systems that collect data over time, can be integrated with other systems, and can be analyzed easily for trends. The goal of this project was to study effective tools and strategies in the design and use of clinical registries with the potential to facilitate quality improvement, value-based purchasing, and public reporting on the quality of care. The research team … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 7 publications
0
25
0
2
Order By: Relevance
“…Table summarizes the main observations of current policies and conditions for QI registries in the USA. The promotion of value‐based purchasing by the Patient Protection and Affordable Care Act has stimulated the participation of providers in registry programmes as a way to offer comparative performance data to payers and purchasers . Some recent US developments actually mirror Swedish registry policies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table summarizes the main observations of current policies and conditions for QI registries in the USA. The promotion of value‐based purchasing by the Patient Protection and Affordable Care Act has stimulated the participation of providers in registry programmes as a way to offer comparative performance data to payers and purchasers . Some recent US developments actually mirror Swedish registry policies.…”
Section: Resultsmentioning
confidence: 99%
“…Still, establishing national registries in such a large country is challenging, and registries have typically been confined to a particular geographical location, organization or self‐selected group of organizations . Whilst registries have not been a major part of national quality strategies, there is a surge of interest in nationwide QI registries , and they are favoured by some recent federal policies .…”
Section: Introductionmentioning
confidence: 99%
“…Registries continued to be used for a variety of purposes and were capturing and measuring the kinds of data and information needed to power a value-based, learning health care delivery system. Given the national emphasis on measuring patient health outcomes, registries responded by developing measures and data collection methods that make implementing these measures feasible [ 14 30 31 ]. Registries provide timely, actionable and specific feedback to participating clinicians, enabling them to understand their performance relative to their peers, both locally and nationally.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008 Drolet et al published a classification system for registries that identified five characteristics of a registry, using the term in its broadest sense: mergeable, standardized longitudinal data from multiple users, including outcomes, collected using a rules-based approach [20]. Klaiman et al examined registry use in 2013 and found that “effective registries were successful in 1 or more of 6 key areas: data standardization, transparency, accuracy/completeness of data, participation by providers, financial sustainability, and/or providing feedback to providers [21]. ” The Australian Commission on Safety and Quality in Health Care has published a framework for quality registries that describes desired registry attributes across domains including data collection, risk adjustment, data security, data quality, governance, ethics & privacy, reporting and funding [22].…”
Section: Prior Work On Clinical Registry Evaluationmentioning
confidence: 99%